Waterproof, windproof and breathable biomimetic membrane and preparation method thereof

By adopting a bionic film with a three-layer composite membrane structure, combined with a honeycomb-like porous membrane modified and organized by polyvinyl alcohol-chitosan hydrogel, the problem of wet and cold feeling in rainy and snowy weather is solved, and the comprehensive performance improvement of waterproof, windproof, breathable and moisture-absorbing and heat-absorbing is achieved.

CN119610839AActive Publication Date: 2025-03-14GAOFAN (ZHEJIANG) INFORMATION TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411827335.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

During outdoor sports, clothing fabrics are easily soaked by rain and snow in rainy weather, resulting in a wet and cold feeling, poor comfort, and it is difficult for the prior art to achieve the comprehensive performance of waterproof, windproof, breathable, and moisture absorption and heat generation at the same time.

Method used

A bionic film with a three-layer composite film structure includes a honeycomb-like porous film modified and sorted with polyvinyl alcohol-chitosan hydrogel as the substrate, and a waterproof and moisture-permeable film is combined on both sides to form excellent waterproof, windproof and breathable properties.

Benefits of technology

It realizes the waterproof and windproof performance of clothing fabrics without sacrificing breathability, and improves the moisture absorption and heating performance of the fabrics after being combined with the fabric, and improves the comfort and functionality of the wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610839A_ABST
    Figure CN119610839A_ABST
Patent Text Reader

Abstract

The invention relates to a waterproof, windproof and breathable biomimetic membrane and a preparation method thereof, and relates to the technical field of composite functional membranes, the biomimetic membrane is a three-layer composite membrane, the specific structure of the biomimetic membrane is that a honeycomb porous membrane is used as a base material, and waterproof and moisture permeable membranes are respectively compounded on two surfaces of the base material to form the biomimetic membrane; wherein the honeycomb porous membrane is modified and finished by polyvinyl alcohol-chitosan hydrogel. The biomimetic membrane provided by the invention is designed based on the bionics principle, the membrane can be endowed with excellent waterproof and windproof properties by taking the two layers of waterproof and moisture permeable membranes as the outer layer of the membrane, and the honeycomb porous membrane of the middle layer is taken as the main body of the membrane, so that the membrane can be endowed with excellent mechanical properties while the air permeability of the membrane is ensured. The biomimetic membrane provided by the invention is high in comprehensive performance, can improve the wearing comfort and functionality of outdoor sportswear, and has a better application prospect in the field of garment fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite functional membranes, and in particular relates to a waterproof, windproof and breathable bionic membrane and a preparation method thereof. Background Art

[0002] When exercising outdoors, people are easily affected by rain and snow. When clothes are soaked by rain, they easily stick to the surface of the human body, which makes people feel cold and damp, and the comfort is poor. Therefore, the most important thing to improve the user experience is to improve the thermal and moisture comfort, waterproofness, windproofness and breathability of clothing fabrics. As consumers' requirements for clothing textiles change from aesthetics and comfort to multifunctional textiles such as antibacterial, heat-generating, warm-keeping, and moisture-conducting, the textile field will also shift its research direction from traditional fabric research to functional textiles, aiming to design clothing with better user experience. At present, the functional improvement methods for clothing fabrics are, on the one hand, coating the fabrics with functional finishing agents, and on the other hand, laminating the fabrics by designing functional films.

[0003] With the continuous research on bionic technology, it is found that some excellent biological characteristics of amphibians have potential bionic application prospects, and functional textiles, especially outdoor sports textiles, have been developed based on this. For example, the bionic film Symbionic proposed by X-Bionic improves air permeability and sweating ability and reduces the risk of overheating by imitating the skin breathing of frogs. Specifically, the skin of amphibians is composed of epidermis and dermis. The inner layer of the epidermis is the germinal layer and the outer layer is the stratum corneum, which can reduce the evaporation of water in the body to a certain extent. In addition, there are many glands in the dermis of anurans, such as mucus glands and serous glands. The mucus glands of some frogs are hollow. When the skin is dehydrated or the environment is low in temperature, it can absorb water vapor in the environment by secreting mucus substances to achieve the purpose of maintaining skin water balance and body temperature balance. It can be seen that the skin tissue morphology of amphibians and anurans is of great research significance for studying and developing functional bionic membranes with excellent performance, improving the wearing comfort and functionality of outdoor sportswear, and enhancing its application prospects in the field of clothing fabrics. Summary of the invention

[0004] The purpose of the present invention is to provide a waterproof, windproof and breathable bionic membrane and a preparation method thereof in order to solve the above problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] As the first aspect of the present invention, the present invention provides a waterproof, windproof and breathable bionic membrane, which is a three-layer composite membrane. The specific structure is formed by using a honeycomb porous membrane as a substrate and compounding waterproof and moisture-permeable membranes on both sides of the substrate; wherein the honeycomb porous membrane is modified and finished by polyvinyl alcohol-chitosan hydrogel.

[0007] As a further optimization scheme of the present invention, the honeycomb porous membrane is a polylactic acid honeycomb porous membrane, and its preparation method comprises the following steps:

[0008] (1) dissolving a certain amount of polylactic acid in a dichloromethane solvent to obtain a casting solution with a concentration of 2-5 wt %;

[0009] (2) at a temperature of 30-35° C. and a relative humidity of 50-80%, after casting a film on a substrate, the substrate is placed in a sealed space, and a saturated aqueous solution of sodium chloride is added to the sealed space to maintain the humidity of the sealed space at 75-80%, and a polylactic acid film is obtained after the solvent evaporates;

[0010] (3) The polylactic acid film is vacuum dried at 50-55°C for 90-120 min to remove the residual solvent.

[0011] As a further optimization scheme of the present invention, the waterproof and breathable membrane is a polytetrafluoroethylene waterproof and breathable membrane, a polyvinylidene fluoride waterproof and breathable membrane or a polytetrafluoroethylene-polyvinylidene fluoride waterproof and breathable membrane.

[0012] As a further optimization scheme of the present invention, the preparation method of the waterproof and breathable membrane is to first add at least one of polytetrafluoroethylene or polyvinylidene fluoride into a solvent, stir for 1-2 hours at 70-90°C until completely dissolved, stand for degassing to obtain a casting liquid, then, scrape the casting liquid onto a substrate, put the substrate into a coagulation bath to form a film after pre-volatilization, rinse in clean water for 12-24 hours, take out the membrane and dry it to obtain it.

[0013] As a further optimization scheme of the present invention, the preparation method of the polyvinyl alcohol-chitosan hydrogel comprises the following steps:

[0014] (1) dissolving a certain amount of chitosan in a 0.1 mol / L acetic acid solution to obtain a chitosan solution;

[0015] (2) adding polyvinyl alcohol powder in an amount of half the mass of chitosan to the chitosan solution, stirring at 80° C. until the polyvinyl alcohol is completely dissolved, cooling to room temperature, stirring overnight to form a uniform mixed solution, adding 0.2 mol / L glutaraldehyde solution dropwise to the mixed solution at 25° C., and continuously stirring for a cross-linking reaction for 60-120 min to obtain a hydrogel solution;

[0016] (3) Under ice bath conditions, phosphoric acid is first added dropwise to the hydrogel solution until the volume percentage of phosphoric acid in the hydrogel solution system is 2-4%, and then propylene glycol is added dropwise to the hydrogel solution until the volume percentage of propylene glycol in the hydrogel solution system is 2-4%. After stirring for 30-60 minutes, the pH value of the hydrogel solution is adjusted to 7.5.

[0017] As a second aspect of the present invention, the present invention also provides a method for preparing the waterproof, windproof and breathable bionic membrane as described above, comprising the following steps:

[0018] (1) placing the honeycomb porous membrane in a polyvinyl alcohol-chitosan hydrogel solution and subjecting it to ultrasonic vibration modification for 60-120 minutes, and drying the honeycomb porous membrane after the modification is completed for later use;

[0019] (2) preparing a waterproof and breathable membrane, coating one side of the waterproof and breathable membrane with a polyurethane adhesive and then compounding it with one side of a honeycomb porous membrane, compounding the other side of the honeycomb porous membrane with the waterproof and breathable membrane in the same manner to obtain a three-layer composite membrane, and laminating the three-layer composite membrane to obtain the bionic membrane.

[0020] As a further optimization scheme of the present invention, the power of the ultrasonic oscillation treatment is 50-70kHz, and the method for drying the honeycomb porous membrane is to dry the honeycomb porous membrane with hot air, the hot air temperature is 40-50°C, the wind speed is 2-5m / s, and the drying time is 60-120min.

[0021] The beneficial effects of the present invention are:

[0022] The bionic membrane provided by the present invention is designed based on the principle of bionics. The specific structure is that the honeycomb porous membrane modified and finished by polyvinyl alcohol-chitosan hydrogel is used as the substrate, and the waterproof and breathable membranes are respectively compounded on both sides of the substrate to form a three-layer composite membrane structure. On the one hand, the waterproof and breathable membrane is used as the outer layer of the bionic membrane to give the membrane excellent waterproof and windproof properties, and the honeycomb porous membrane in the middle layer as the main body of the membrane can ensure the air permeability of the membrane while also giving the membrane excellent mechanical properties. On the other hand, after the honeycomb porous membrane of the bionic membrane is modified and finished by polyvinyl alcohol-chitosan hydrogel, the moisture absorption and heat generation performance of the fabric can be further improved after the bionic membrane is compounded with the fabric.

[0023] The bionic membrane provided by the present invention has strong comprehensive performance, can improve the wearing comfort and functionality of outdoor sportswear, and has good application prospects in the field of clothing fabrics. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic structural diagram of the waterproof, windproof and breathable bionic membrane provided by the present invention. DETAILED DESCRIPTION

[0025] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0026] 1. Materials and Methods

[0027] Specific methods not specified in this example can be carried out according to conventional methods, and other materials, reagents, etc. used can be obtained through commercial channels unless otherwise specified.

[0028] 1. Preparation of waterproof, windproof and breathable bionic membrane

[0029] 1.1 Preparation of honeycomb porous membrane

[0030] The honeycomb porous membrane is specifically a polylactic acid honeycomb porous membrane. The preparation method of the polylactic acid honeycomb porous membrane is as follows: polylactic acid is dissolved in a dichloromethane solvent to obtain a casting liquid with a concentration of 2-5wt%. In this embodiment, the concentration of the casting liquid is preferably 4wt%. Then, at a temperature of 30-35°C and a relative humidity of 50-80%, the casting liquid is dropped on a substrate to form a film. In this embodiment, the temperature is preferably 35°C and the relative humidity is 60%. The substrate is placed in a sealed space, and a saturated aqueous solution of sodium chloride is added to the sealed space to maintain the humidity in the sealed space at 75-80%. In this embodiment, it is preferably 75%. After the solvent evaporates, a polylactic acid film is obtained, and the polylactic acid film is vacuum dried at a temperature of 50-55°C for 90 minutes to remove the residual solvent. The drying temperature in this embodiment is preferably 50°C. The thickness of the honeycomb porous membrane is about 50μm.

[0031] 1.2. Preparation of waterproof and breathable membrane

[0032] The waterproof and breathable membrane is a polytetrafluoroethylene waterproof and breathable membrane, a polyvinylidene fluoride waterproof and breathable membrane or a polytetrafluoroethylene-polyvinylidene fluoride waterproof and breathable membrane. In this embodiment, the polyvinylidene fluoride waterproof and breathable membrane is taken as an example. First, polyvinylidene fluoride is added to the solvent, stirred at 90°C for 2h until it is completely dissolved, and then the casting liquid is obtained by standing and degassing. The solvent is N, N-dimethylformamide. In this embodiment, the casting liquid is preferably 5wt%. Then, the casting liquid is scraped onto the substrate. After pre-volatilization, the substrate is placed in a coagulation bath to form a film, and then rinsed in clean water for 12h. The film is taken out and dried to obtain a waterproof and breathable membrane with a thickness of about 120μm.

[0033] 1.3. Modification and finishing of honeycomb porous membrane

[0034] (1) Preparation of polyvinyl alcohol-chitosan hydrogel

[0035] First, chitosan was dissolved in an acetic acid solution with a concentration of 0.1 mol / L to obtain a chitosan solution, and the mass volume ratio of chitosan to acetic acid solution was 4:1 (g:L). Then, polyvinyl alcohol powder in an amount of half the mass of chitosan was added to the chitosan solution, and then stirred at 80°C until the polyvinyl alcohol was completely dissolved, cooled to room temperature, and stirred overnight to form a uniform mixed solution. Finally, a glutaraldehyde solution with a concentration of 0.2 mol / L was added dropwise to the mixed solution at 25°C, and the cross-linking reaction was stirred for 120 minutes to obtain a hydrogel solution.

[0036] Under ice bath conditions, phosphoric acid is first added dropwise to the hydrogel solution until the volume percentage of phosphoric acid in the hydrogel solution system is 2-4%, preferably 2% in this embodiment, and then propylene glycol is added dropwise to the hydrogel solution until the volume percentage of propylene glycol in the hydrogel solution system is 2-4%, preferably 4% in this embodiment, and the pH value of the hydrogel solution is adjusted to 7.5 after stirring for 30-60 minutes.

[0037] (3) Modification and finishing

[0038] The honeycomb porous membrane is placed in a polyvinyl alcohol-chitosan hydrogel solution and subjected to ultrasonic oscillation modification for 120 minutes. After the modification, the honeycomb porous membrane is dried. The power of the ultrasonic oscillation treatment can be selected to be 50-70kHz. In the present embodiment, 60kHz is preferred. The method for drying the honeycomb porous membrane is as follows: the honeycomb porous membrane is dried with hot air. The hot air temperature is 40-50°C, the wind speed is 2-5m / s, and the drying time is 60-120min. In the present embodiment, the preferred hot air temperature is 45°C, the wind speed is 4m / s, and the drying time is 60min.

[0039] 1.4 Preparation of biomimetic membrane

[0040] After coating one side of the waterproof and breathable membrane with a polyurethane adhesive, it is composited with one side of the honeycomb porous membrane obtained by the modification and finishing in step 1.3. Then, the other side of the honeycomb porous membrane is composited with the waterproof and breathable membrane according to the same operation to obtain a three-layer composite membrane. The three-layer composite membrane is laminated to obtain the bionic membrane. The polyurethane adhesive is sprayed on the surface of the waterproof and breathable membrane. The thickness of the bionic membrane finally obtained does not exceed 350 μm. The specific implementation method of using a polyurethane adhesive to composite the honeycomb porous membrane between two waterproof and breathable membranes is a method for preparing a composite membrane known in the art. The present invention does not make any improvements to this, so it will not be described in detail.

[0041] The schematic diagram of the structure of the biomimetic membrane prepared in steps 1.1-1.4 is shown in Figure 1 As shown, Figure 1The circled part is a schematic diagram of the structure of the enlarged honeycomb porous membrane. It can be seen that the pore structure of the honeycomb porous membrane presents a uniform honeycomb shape, the pore sizes are uniform and arranged regularly, and the polyvinyl alcohol-chitosan hydrogel is attached to the pore structure of the honeycomb porous membrane after modification.

[0042] 2. Verification test

[0043] In order to verify the influence of the structural composition of the bionic membrane on its performance, the bionic membrane prepared by steps 1.1-1.4 was counted as membrane sample A.

[0044] Then, the structural composition of the bionic membrane is designed as follows:

[0045] Membrane sample B: The difference from membrane sample A is that the polylactic acid fiber membrane prepared by the electrospinning preparation method is used instead of the honeycomb porous membrane.

[0046] The specific preparation method of the polylactic acid fiber membrane is as follows: dissolving polylactic acid in a dichloromethane solvent to obtain a spinning solution with a concentration of 4wt%, using a 10mL syringe to absorb more than 3mL of the spinning solution, fixing the syringe to the propulsion pump of the electrospinning machine, adjusting the distance between the needle and the receiving plate to 16cm, adjusting the voltage of the high-voltage power supply to 16kV, the spinning rate to 0.5mL / h, the spinning volume to 3mL, and the ambient temperature to 25°C; after the spraying is completed, the spinning membrane is heat treated at 50°C for 4h.

[0047] Film sample C: The difference from film sample A is that the polyvinyl alcohol-chitosan hydrogel is not modified.

[0048] Membrane sample D: The difference from membrane sample A is that the preparation method of the polyvinyl alcohol-chitosan hydrogel used is different. Specifically, the preparation method of the polyvinyl alcohol-chitosan hydrogel used in membrane sample D is: first dissolve chitosan in an acetic acid solution with a concentration of 0.1 mol / L to obtain a chitosan solution, and the mass volume ratio of chitosan to acetic acid solution is 4:1 (g:L), and then add polyvinyl alcohol powder in an amount of half the mass of chitosan to the chitosan solution, and then stir at 80°C until the polyvinyl alcohol is completely dissolved, cool to room temperature, stir overnight to form a uniform mixed solution, and finally add glutaraldehyde solution with a concentration of 0.2 mol / L dropwise to the mixed solution at 25°C, and continue stirring for 120 minutes for the cross-linking reaction to obtain a hydrogel solution.

[0049] Film sample E: The difference from film sample A is that the preparation method of the polyvinyl alcohol-chitosan hydrogel used is different. Specifically, the preparation method of the polyvinyl alcohol-chitosan hydrogel used in film sample E is as follows: first, chitosan is dissolved in an acetic acid solution with a concentration of 0.1 mol / L to obtain a chitosan solution, and the mass volume ratio of chitosan to acetic acid solution is 4:1 (g:L), and then polyvinyl alcohol powder in an amount of half the mass of chitosan is added to the chitosan solution, and then stirred at 80°C until the polyvinyl alcohol is completely dissolved, cooled to room temperature, and stirred overnight to form a uniform mixed solution, and finally a glutaraldehyde solution with a concentration of 0.2 mol / L is added dropwise to the mixed solution at 25°C, and the cross-linking reaction is stirred for 120 minutes to obtain a hydrogel solution;

[0050] Under ice bath conditions, glycerophosphoric acid is first added dropwise to the hydrogel solution until the glycerophosphoric acid in the hydrogel solution system is 2%, and the pH value of the hydrogel solution is adjusted to 7.5 after stirring for 30-60 minutes.

[0051] Membrane sample F: The difference from membrane sample A is that during the modification and finishing of the honeycomb porous membrane, the honeycomb porous membrane is placed in a polyvinyl alcohol-chitosan hydrogel solution for immersion treatment and modification for 120 minutes. After the modification is completed, the honeycomb porous membrane is dried. The drying method for the honeycomb porous membrane is consistent with the drying method for membrane sample A.

[0052] Control film sample: The difference from film sample A is that it does not contain the honeycomb porous film modified by polyvinyl alcohol-chitosan hydrogel, and only a polyurethane adhesive is coated on one side of one waterproof and breathable film and then composited on another waterproof and breathable film.

[0053] 2.1 Waterproof performance test

[0054] (1) Hydrostatic pressure test

[0055] The hydrostatic pressure resistance test was carried out on the membrane samples AF and the control membrane sample according to GB / T 4744-2013. The test method is as follows: wipe off the test water on the surface of the clamped sample, clamp the sample so that the front of the sample is in contact with the water. Apply a continuously increasing water pressure to the sample at a water pressure increase rate of 60cm H2O / min, and observe the water seepage phenomenon. During the pressure increase process, stop the pressure increase when the third water droplet appears on the sample, and record the hydrostatic pressure value at this time. Repeat 5 groups for each membrane sample, and take the average of the results.

[0056] (2) Water resistance test

[0057] The test was conducted according to the test method provided in GB / T4745-2012 "Testing and evaluating the waterproof performance of textiles - Water-impregnated method". Each film sample was repeated 5 times and the results were averaged. The water-impregnated grades are divided into: 2-3: poor anti-wetting grade; 3: anti-wetting performance; 3-4: good anti-wetting performance; 4: very good anti-wetting performance; 4-5, 5: excellent anti-wetting performance.

[0058] The results are shown in Table 1.

[0059] Table 1. Statistics of waterproof performance test results of membrane samples

[0060]

[0061]

[0062] As can be seen from Table 1, the structures of film samples AF are all three-layer composite films, and the outermost layer of the film sample is a polyvinylidene fluoride waterproof and breathable film. The pores on the surface of the polyvinylidene fluoride waterproof and breathable film present a mesh-like fine porous structure. Its waterproof and breathable properties are based on the fact that the pore size of the membrane is smaller than the size of raindrops but larger than the size of water vapor molecules, and water droplets do not pass through and have waterproof properties. Therefore, film samples AF have excellent anti-wetting properties, and the anti-wetting level is 4-5. The control film sample is a composite of two layers of polyvinylidene fluoride waterproof and breathable films. Due to the waterproof properties of the polyvinylidene fluoride waterproof and breathable membrane, the control film sample also has excellent anti-wetting properties.

[0063] In addition, it can be seen from Table 1 that there is a difference in the hydrostatic pressure resistance value between the film sample AF and the control film sample. The hydrostatic pressure resistance value of the film sample AF is better than that of the control film sample. The reason is that the film sample AF is a three-layer composite film, and the control film sample is a double-layer composite film. The hydrostatic pressure resistance values ​​of the film samples B and F are slightly higher than those of the other film samples. The middle layer of the film sample B is a polylactic acid fiber membrane, which is made by electrospinning. Although the middle layer of the film sample F is a honeycomb porous membrane, it is not subjected to ultrasonic oscillation treatment during modification and finishing. Therefore, it is speculated that the change in the structural density of the film sample middle layer is the reason why the hydrostatic pressure resistance values ​​of the film samples B and F are slightly higher than those of the other film samples.

[0064] 2.2. Air permeability test

[0065] The air permeability of the film samples was characterized by water vapor permeability, and the water vapor permeability of film samples AF and control film samples was tested according to ISO 2528-1995 "Gravimetric method for the determination of water vapor permeability of thin sheet materials". The results are shown in Table 2.

[0066] Table 2. Statistics of air permeability test results of membrane samples

[0067]

[0068]

[0069] As can be seen from Table 2, the water vapor permeability of film sample AF is lower than that of the control film sample. The reason is that: film sample AF is a three-layer composite film, while the control film sample is a double-layer composite film. The air permeability of the double-layer composite film is better than that of the three-layer composite film. Compared with film sample AF, the water vapor permeability of film sample A is less reduced than that of the control film sample. It can be seen that the honeycomb porous film has a smaller impact on the overall air permeability of the film sample. The water vapor permeability of film sample B is reduced more than that of film sample A. It can be seen that the polylactic acid fiber membrane prepared by electrospinning has an adverse effect on the air permeability of the film sample, which is not as good as the polylactic acid honeycomb porous membrane. In addition, although the middle layer of film sample F is a honeycomb porous membrane, it was not subjected to ultrasonic oscillation treatment during modification and finishing, which would damage the pore structure of the film sample. It can also be seen from the table that its water vapor permeability is reduced to a certain extent compared with film sample A.

[0070] 2.3 Mechanical properties test

[0071] According to GB / T1040.3-2006, the film samples AF and the comparative film samples were made into standard dumbbell specimens, and the tensile strength (transverse tensile strength and longitudinal tensile strength) and elongation at break of the film samples were measured at a speed of 100 mm / min. The results are shown in Table 3.

[0072] Table 3. Statistics of mechanical properties test results of film samples

[0073]

[0074] From the results in Table 3, it can be seen that compared with the control film sample, the tensile strength and elongation at break of film sample AF have been improved to a certain extent. The reason is that the setting of the film sample middle layer makes the film sample more resistant to stretching and improves the mechanical properties. Compared with film sample A, the tensile strength and elongation at break of film sample C have decreased. It can be seen that the modification and finishing of the honeycomb porous membrane by polyvinyl alcohol-chitosan hydrogel has a positive effect on improving the overall mechanical properties of the film sample. The tensile strength and elongation at break of film sample A are slightly lower than those of film sample B and film sample F, but the difference is not significant.

[0075] 2.4 Application test

[0076] The film sample AF and the control film sample were laminated on one side of the polyester fabric by a lamination process to prepare the laminated fabric AF and the control laminated fabric, and the moisture absorption and heat generation performance of the laminated fabric was tested.

[0077] The test equipment uses an electric constant temperature blast drying oven, a constant temperature and humidity chamber, and a temperature sensor. Referring to the standard GB / T29866-2013 "Test method for moisture absorption and heat generation performance of textiles", 6 fabric samples are cut from each type of coated fabric, and any two of the fabric samples are pasted together with the reverse sides. The three sides of the samples pasted together with the reverse sides are sewn together using polyester thread using the flat seam method to form a bagged sample. During the test, the temperature sensor is placed in the bagged sample.

[0078] Place the bagged sample to be used in the test in an electric constant temperature blast drying oven and dry it for 2 hours. After drying, place it in a drying dish containing anhydrous calcium chloride, ensure that the drying dish is vacuum sealed, place it in a 20℃ environment for 2 hours, and then place it in a constant temperature and humidity box at 20℃ and 90% humidity. Use a temperature sensor to measure the sample, measure it every 15s, and measure the temperature for 1 hour. During the measurement process, the temperature fluctuation in the box should be minimized to avoid affecting the test. After the test, compare it with the temperature of the blank test group and subtract the temperature measurement value of the blank test group to calculate the maximum temperature rise value and average temperature rise value of each group of coated fabrics within 30 minutes.

[0079] The results are shown in Table 4.

[0080] Table 4. Statistics of test results of moisture absorption and heat generation performance of coated fabrics

[0081]

[0082] It can be seen from Table 4 that the hygroscopic and heat-generating properties of the coated fabric AF are better than those of the control coated fabric. It can be seen that the structure of the film used in the coated fabric has a certain degree of influence on the hygroscopic and heat-generating properties of the fabric itself. By comparing the coated fabric A and the coated fabric C, it can be seen that the hydrogel modification and finishing of the honeycomb porous film of the film-like intermediate layer has a positive effect on improving the hygroscopic and heat-generating properties of the fabric. At the same time, by comparing the coated fabric DE, it can be seen that the preparation method of the polyvinyl alcohol-chitosan hydrogel has a certain correlation with its improvement of the hygroscopic and heat-generating properties of the fabric. The bionic membrane provided by the present invention has an improvement effect on the hygroscopic and heat-generating properties of the fabric after being compounded with the fabric, and can give the fabric a better use experience. The fabric can be used to prepare sportswear to improve the wearing comfort.

[0083] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A waterproof, windproof and breathable bionic membrane, characterized in that: The bionic membrane is a three-layer composite membrane, and its specific structure is formed by using a honeycomb porous membrane as a substrate and compounding waterproof and breathable membranes on both sides of the substrate; wherein the honeycomb porous membrane is modified and finished by polyvinyl alcohol-chitosan hydrogel.

2. A waterproof, windproof and breathable bionic membrane according to claim 1, characterized in that: The honeycomb porous membrane is a polylactic acid honeycomb porous membrane, and its preparation method comprises the following steps: (1) dissolving a certain amount of polylactic acid in a dichloromethane solvent to obtain a casting solution with a concentration of 2-5 wt %; (2) at a temperature of 30-35° C. and a relative humidity of 50-80%, after the casting liquid droplets are cast on the substrate to form a film, the substrate is placed in a sealed space, and a saturated aqueous solution of sodium chloride is added into the sealed space to maintain the humidity in the sealed space at 75-80%, and a polylactic acid film is obtained after the solvent evaporates; (3) The polylactic acid film is vacuum dried at 50-55°C for 90-120 min to remove the residual solvent.

3. The waterproof, windproof and breathable bionic membrane according to claim 1, characterized in that: The waterproof and breathable membrane is a polytetrafluoroethylene waterproof and breathable membrane, a polyvinylidene fluoride waterproof and breathable membrane or a polytetrafluoroethylene-polyvinylidene fluoride waterproof and breathable membrane.

4. The waterproof, windproof and breathable bionic membrane according to claim 3, characterized in that: The preparation method of the waterproof and breathable membrane is as follows: first, at least one of polytetrafluoroethylene or polyvinylidene fluoride is added into a solvent, stirred at 70-90°C for 1-2 hours until completely dissolved, and allowed to stand for degassing to obtain a casting liquid, and then, the casting liquid is scraped onto a substrate, and after pre-volatilization, the substrate is placed in a coagulation bath to form a film, and then rinsed in clean water for 12-24 hours, and the membrane is taken out and dried to obtain the film.

5. The waterproof, windproof and breathable bionic membrane according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol-chitosan hydrogel is specifically as follows: (1) dissolving a certain amount of chitosan in an acetic acid solution with a concentration of 0.1 mol / L to obtain a chitosan solution; (2) adding polyvinyl alcohol powder in an amount of half the mass of chitosan to the chitosan solution, stirring at 80° C. until the polyvinyl alcohol is completely dissolved, cooling to room temperature, stirring overnight to form a uniform mixed solution, adding 0.2 mol / L glutaraldehyde solution dropwise to the mixed solution at 25° C., and continuously stirring for a cross-linking reaction for 60-120 min to obtain a hydrogel solution; (3) Under ice bath conditions, phosphoric acid is first added dropwise to the hydrogel solution until the volume percentage of phosphoric acid in the hydrogel solution system is 2-4%, and then propylene glycol is added dropwise to the hydrogel solution until the volume percentage of propylene glycol in the hydrogel solution system is 2-4%. After stirring for 30-60 minutes, the pH value of the hydrogel solution is adjusted to 7.

5.

6. A method for preparing the waterproof, windproof and breathable bionic membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) placing the honeycomb porous membrane in a polyvinyl alcohol-chitosan hydrogel solution and subjecting it to ultrasonic vibration modification for 60-120 minutes, and drying the honeycomb porous membrane after the modification is completed for later use; (2) preparing a waterproof and breathable membrane, coating one side of the waterproof and breathable membrane with a polyurethane adhesive and then compounding it with one side of a honeycomb porous membrane, compounding the other side of the honeycomb porous membrane with the waterproof and breathable membrane in the same manner to obtain a three-layer composite membrane, and laminating the three-layer composite membrane to obtain the bionic membrane.

7. The method for preparing a waterproof, windproof and breathable bionic membrane according to claim 6, characterized in that: In step (1), the power of the ultrasonic oscillation treatment is 50-70kHz, and the method for drying the honeycomb porous membrane is to dry the honeycomb porous membrane with hot air, the hot air temperature is 40-50°C, the wind speed is 2-5m / s, and the drying time is 60-120min.

Citation Information

Patent Citations

  • High-selectivity asymmetric moisture-permeable film as well as preparation method and application thereof

    CN101947416A

  • Preparation method of anti-static polyvinylidene fluoride / polylactic acid composite porous fiber membrane

    CN105970486A

  • Washable waterproof moisture-permeable foam adhesive laminated fabric and preparation method thereof

    CN111516311A

  • Antibacterial waterproof breathable film and preparation method thereof

    CN112662006A

  • Multi-layer embedded waterproof membrane and preparation method thereof

    CN112663348A